2012
DOI: 10.1504/ijewm.2012.044161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various leachate recirculation strategies on batch anaerobic digestion of solid substrates

Abstract: Various leachate recirculation strategies were applied to a batchwise operated one-stage solid-phase digestion system in laboratory-scale tests. Comparative experiments with both continuous and intermittent leachate recirculation revealed no advantages of a continuous flow. Results suggest that leachate recirculation should not be carried out continuously during process initialisation when methanogenesis is the rate-limiting step. Continuous watering resulted in the accumulation of Volatile Fatty Acids (VFA) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 73 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…It was found that leaching is favorable for the anaerobic decomposition of food waste. However, depending on the frequency of recirculation, it can increase acidogenesis, which may result in the inhibition of methanogenesis (Kusch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that leaching is favorable for the anaerobic decomposition of food waste. However, depending on the frequency of recirculation, it can increase acidogenesis, which may result in the inhibition of methanogenesis (Kusch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal conditions are difficult to be determined and to be fulfilled at farm-scale, which increases the risk of incomplete degradation in this simple fermenter type with no substrate mixing. It has been demonstrated that during process initiation discontinuous leachate recirculation is more favourable than continuous watering (Kusch et al, 2012;Martin, 1999;Vavilin et al, 2002Vavilin et al, , 2003Veeken and Hamelers, 2000), which is assumed to be the result of encouraging methanogenic areas to expand throughout the whole digester, while continuous watering bears the risk to spread acidification. In addition, it was demonstrated that for the process type discussed here there is no beneficial effect of continuous water circulation compared to discontinuous watering throughout the whole digestion process (Kusch et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As the substrate in Mix II (Dung) was completely mixed with the inoculum, acidification presumably took place throughout the digester and thus being irreversible. This underlines the advantage of bottom inoculation or layered inoculation, where acidification can be locally limited, so that active zones are maintained and complete process failure can be prevented [14,23].…”
Section: Performance Of the Second Ssad Runmentioning
confidence: 99%
“…Moreover, the low water content in SSAD can limit mass transfer of intermediate compounds in the digester, which can significantly slow down the digestion process [13]. Additionally, the high risk of irreversible acidification requires a high inoculum to substrate (I/S) ratio [14]. In order to accelerate mass transfer and reduce the risk of acidification SSAD is often operated in two-stage digesters and/or with leachate recirculation [15,16].…”
Section: Introductionmentioning
confidence: 99%